Practising piety in a (post-) pandemic time: A spatial reading of piety in Psalm 66 from the perspectives of memory and bodily imagery - Sutton, Lodewyk (HTS teologiese studies, 2021)
Situated in the larger collection of Psalms 51–72, also known as the second Davidic Psalter, the smaller group of Psalms 65–68 is found. This smaller collection of psalms can be classified mostly as psalms of praise and thanksgiving. The relation and compositional work in this cluster of psalms become apparent on many points in the pious expressions between groups and persons at prayer, especially in the universal praise of God, and in the imagery referring to the exodus, the Jerusalem cult and blessing. Such piety becomes most discernible in the imagery and expressions in Psalm 66. The psalm’s two main sections may be described as praise, with verses 1–12 being praise by the group or the ‘we’, and verses 13–20 being praise by the individual or the ‘I’. Personal or individual piety and private piety are expressed by the desire of the ‘we’ and the ‘I’, and the experienced immediacy to God by transposing the past into the present through the memory of the exodus narrative, the Jerusalem cultic imagery and the use of body imagery. In this research article, an understanding of piety in Psalm 66 in terms of the memory of past events and body imagery is discussed from a perspective of space and appropriated for a time of (post-) pandemic where normal or traditional ecclesiological formal practices cannot take place.Contribution: This article makes an interdisciplinary contribution based on knowledge from the Psalms in the Old Testament, social anthropology, literary spatial theories and practical theological perspectives on the church in order to contribute to the relevance and practice of theology today, during a time of turmoil and a global pandemic.